L’analyse conversationnelle comme approche "sociale" de l’acquisition des langues secondes: une illustration empirique - Pochon-Berger, Evelyne (Travaux neuchâtelois de linguistique, 2011)
This paper examines Conversation Analysis as applied to the field of Second Language Acquisition (SLA). The epistemological framework of CA is first presented and then exemplified through the study of disagreements accomplished by lower intermediate level learners of French L2. Micro-sequential analyses are carried out on a corpus of classroom interactions. The analyses shed new light on practices which have been the focus of previous studies in SLA. The analyses show how learners manage to finely tune their disagreement to the local circumstances by means of diverse resources (e.g. sequential, prosodic), while at the linguistic level, the disagreements appear direct and explicit (essentially turn-initial "no") – which has been interpreted in earlier research as an indicator of limited competence in the L2. On the basis of these results, we discuss specific contributions of Conversation Analysis to SLA research, as well as its limits with regards to other socially oriented approaches to SLA.